Inequality Measures: The Kolkata Index in Comparison With Other Measures - Banerjee, Suchismita; Chakrabarti, Bikas K.; Mitra, Manipushpak; Mutuswami, Suresh (Frontiers in Physics, 2020)
We provide a survey of the Kolkata index of social inequality (GC2014, CG2017, BCMM2020), focusing in particular on income inequality. Based on the observation that inequality functions (such as the Lorenz function), giving the measures of income or wealth against that of the population, to be generally nonlinear, we show that the fixed point (like Kolkata index k) of such a nonlinear function (or related, like the complementary Lorenz function) offer better measure of inequality than the average quantities (like Gini index). Indeed the Kolkata index can be viewed as a generalized Hirsch index for a normalized inequality function and gives the fraction k of the total wealth possessed by the rich 1-k fraction of the population. We analyze the structures of the inequality indices for both continuous and discrete income distributions. We also compare the Kolkata index to some other measures like the Gini coefficient and the Pietra index. Lastly, we provide some empirical studies which illustrate the differences between the Kolkata index and the Gini coefficient.